HIV/AIDS and Indian youth - a review of the literature (1980 - 2008) - Anita Nath (Taylor & Francis Group, 2009)
The main objective of this article is to provide a comprehensive overview of the situation regarding HIV/AIDS among youth in India, and explore the possible strategies that could be effective in combating the spread of this disease. India is in the grip of the HIV/AIDS epidemic, with an increasing number of infections being reported among youth, who comprise a quarter of the population but account for almost one-third of the HIV/AIDS burden. The prevalence in young women appears to be on the rise. Although the majority of youth are aware of the disease, a number of myths and misconceptions still prevail. Furthermore, or as a consequence, a higher percentage of young males report engaging in premarital sexual activity compared with females. Even though condom awareness is fairly high, condom usage is low. Of late, sex tourism and its implications for the HIV/AIDS epidemic present an increasing concern. Indian youth appear to hold negative attitudes towards HIV testing and people living with HIV/AIDS. Although a number of preventive and control programmes and policies exist, these need further strengthening and evaluation.